In-vitro research method for preventing and treating enamel chalk spots by using ZIF-8 at nHA modified invisible appliance

By modifying the ZIF-8@nHA material on the surface of the invisible brace, the challenge of preventing and treating enamel chalky spots during the invisible treatment is solved, and the long-term maintenance of enamel remineralization effect and improving antibacterial properties are achieved.

CN119818736APending Publication Date: 2025-04-15GUIZHOU PROVINCIAL PEOPLES HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510030874.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

There are challenges in the prevention and control of enamel chalky spots during invisible correction, and the existing technology is difficult to effectively prevent and inhibit the occurrence of enamel demineralization and chalky spots.

Method used

By synthesizing ZIF-8@nHA remineralization material and modifying it to the surface of invisible braces, the PH response of the material, Zn2+ antibacterial properties and loaded exogenous nHA provide a source of mineralized substances, forming a dual-track effect that reduces demineralization and promotes remineralization.

Benefits of technology

In a low exchange and low flow saliva environment, the appropriate calcium and phosphorus ion concentration on the enamel surface is maintained for a long time, the remineralization effect is maintained, and the antibacterial performance of invisible braces and the accuracy of targeted remineralization treatment is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119818736A_ABST
    Figure CN119818736A_ABST
Patent Text Reader

Abstract

The invention relates to the field of dental appliances, and discloses an in-vitro research method for preventing and treating enamel chalk spots by using a ZIF-8-nHA modified invisible appliance, which comprises the following steps of: firstly, dissolving 2-methylazole in 50mL of absolute methanol solution to obtain a solution A; zn (NO3) 2.6 H2O is dissolved in 50 mL of absolute methanol to serve as a solution B; slowly dropwise adding the solution A into the solution B, and performing centrifugal separation to obtain white ZIF-8 nanocrystals; the white ZIF-8 nanocrystal is subjected to a one-step drug loading method, and ZIF-8 (at) nHA is obtained; growing and modifying ZIF-8 (at) nHA on the surface of the tooth socket to obtain a ZIF-8 (at) nHA modified tooth socket; carrying out demineralization on the ZIF-8 (at) nHA modified tooth socket by utilizing an artificial demineralization liquid to obtain an enamel demineralization model; the ZIF-8 (at) nHA remineralization material is synthesized and modified to the surface of an invisible brace, the effect of preventing and treating non-caries early lesion (WSL) of an invisible appliance is explored, a new thought is found for reducing the WSL of an invisible correction patient, key elements such as the load concentration and the controlled release time of a mineralizer for stable remineralization are explored, and an experimental basis is provided for realizing clinical transformation application as soon as possible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of dental braces, and in particular to an in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace. Background Art

[0002] Tooth enamel is an orderly biomineralized tissue. The "dynamic balance of demineralization-remineralization" is the basic characteristic of the tooth surface. In the natural oral cavity, there is a mineralization deposition mechanism that obtains calcium and phosphorus from saliva to protect the integrity of the tooth surface structure. Once the "demineralization-remineralization" balance on the tooth surface is broken, the integrity of the tooth surface is destroyed, leading to the occurrence of caries or non-caries early lesions (WSL). At present, the clinical treatment methods of WSL mainly include remineralization therapy and aesthetic restoration therapy, which are suitable for mild and moderate to severe stages of lesions, respectively. Effective plaque control is the premise and guarantee for preventing the occurrence and development of WSL. Reversing non-caries early lesions such as chalk plaque, remineralization therapy has received more and more attention. There is an urgent need for new mineralization preparations and optimized drug delivery methods to maximize the retention of tooth hard tissues and reduce the continuous destruction of tooth hard tissues. Therefore, enhancing the antibacterial properties of invisible braces and maintaining the mineral ion concentration on the tooth surface may help overcome the risk of WSL or (and) inhibit its development during invisible correction.

[0003] The clinical transformation application of enamel biomimetic mineralization mainly revolves around the continuous accumulation of relatively high concentrations of mineralizers around tooth demineralized lesions, such as increasing the affinity of the enamel surface for salivary calcium and phosphate ions, hydrogel carriers, solvent evaporation and concentrated mineralizing preparations, etc. The clinical application products of enamel remineralization mainly include fluoride preparations and non-fluoride mineralizing preparations. Fluoride preparations and their related complex products still occupy a dominant position in treatment and are the "gold standard" for remineralization therapy. In the future, remineralization therapy urgently needs research breakthroughs in both counteracting biofilm interference and intelligent perception and response to the oral environment.

[0004] This study is based on the design idea of ​​"providing exogenous mineral raw materials to induce remineralization". The proposed ZIF-8@nHA is to load nanohydroxyapatite (nHA) onto the ZIF-8 skeleton and then use it to modify the surface of invisible braces. The nHA non-fluoride preparation was selected as a mineralizer, mainly considering that nHA is the most widely used calcium-phosphate remineralization preparation. However, due to the single flushing of saliva in the mouth, the mineralized material on the tooth surface is insufficient, and it is not easy to maintain the remineralization effect for a long time.

[0005] This study intends to synthesize the MOFs material ZIF-8, load it with the mineralizer nHA, and modify the surface of the invisible braces material thermoplastic polyurethane (TPU). The material's pH response, Zn2+ antibacterial properties, and the loaded exogenous nHA will be used to provide a source of mineralized substances, thereby forming a dual-track effect of reducing demineralization and promoting remineralization, combining prevention and treatment to jointly solve the adverse events of WSL in orthodontic treatment. Summary of the invention

[0006] The present invention aims to provide an in vitro research method for preventing and treating enamel chalky plaque with ZIF-8@nHA modified invisible braces. By synthesizing ZIF-8@nHA remineralization material and modifying it on the surface of invisible braces, the effectiveness of invisible braces in preventing and treating WSL is explored, new ideas are sought to reduce WSL in invisible braces patients, and key factors such as the mineralizer loading concentration and controlled release time for stable remineralization are explored, providing an experimental basis for the early realization of clinical transformation and application.

[0007] In order to achieve the above object, the present invention provides the following method:

[0008] The in vitro research method of the present invention for preventing and treating enamel chalky plaque with a ZIF-8@nHA modified invisible orthodontic appliance is as follows:

[0009] Take 2-methylimidazole and dissolve it in 50 mL of anhydrous methanol solution to obtain solution A;

[0010] Dissolve Zn(NO3)2·6H20 in 50 mL of anhydrous methanol as solution B;

[0011] The A solution is slowly added dropwise to the B solution, and white ZIF-8 nanocrystals are obtained by centrifugation;

[0012] A one-step drug loading method is used on the white ZIF-8 nanocrystals to obtain ZIF-8@nHA;

[0013] Growing and modifying the ZIF-8@nHA on the surface of the brace to obtain a ZIF-8@nHA modified brace;

[0014] The ZIF-8@nHA modified dental cap was demineralized using an artificial demineralizing solution to obtain a demineralized enamel model.

[0015] Preferably, 2-methylimidazole is dissolved in 50 mL of anhydrous methanol solution and then subjected to ultrasonic homogenization to obtain solution A.

[0016] Preferably, the dosage ratio of the 2-methylpyrazole in the A solution and the Zn(NO3)2·6H20 in the B solution is 8:1.

[0017] Preferably, the A solution is slowly added dropwise to the B solution to obtain a mixed solution, and the mixed solution is stirred at room temperature for 1 hour, allowed to stand for 10-14 hours after stirring, and then centrifuged to obtain white ZIF-8 nanocrystals.

[0018] Preferably, the white ZIF-8 nanocrystals are subjected to a one-step drug loading method to obtain ZIF-8@nHA encapsulated nHA with a particle size of 20 nm.

[0019] Preferably, before the ZIF-8@nHA is grown and modified on the surface of the braces, the braces need to be surface hydroxylated first, and the surface hydroxyl groups are increased by surface modification with dopamine for the anchoring attachment of the ZIF-8@nHA; the ZIF-8@nHA is grown and decorated on the braces that have been surface hydroxylated to obtain ZIF-8@nHA modified braces.

[0020] Preferably, the step of demineralizing the ZIF-8@nHA modified braces with an artificial demineralizing solution to obtain enamel demineralization modeling comprises: selecting premolars with complete apical development, complete enamel development, good gloss, no caries, no fluoride spots and tetracycline teeth, no hidden cracks in teeth, and no pulp treatment; cleaning the pigment deposits, surface soft tissues and dental calculus on the surface of the premolars, immersing them in medical saline, and storing them in a refrigerator at 4°C, changing the immersion liquid every week, and the storage time does not exceed one month; setting a 4mm×4mm experimental window area in the central area of ​​the buccal surface of the ex vivo crown of each premolar, coating the remaining areas with a layer of acid-resistant nail polish, and embedding with self-curing resin to obtain ex vivo tooth samples; randomly selecting 5 ex vivo tooth samples from 50 ex vivo tooth samples as normal teeth as a control test, and randomly dividing the remaining 45 ex vivo tooth samples into 3 groups, with 15 ex vivo tooth samples in each group being demineralized until chalky spots appear on the tooth surface.

[0021] Preferably, before setting a 4mm×4mm central area of ​​the buccal surface of the ex vivo crown of each premolar as the experimental window area, the method further includes polishing the ex vivo buccal surface of the premolar with 800 mesh, 1200 mesh, and 2400 mesh carbon silicon sandpaper in sequence until the ex vivo buccal surface becomes a smooth mirror surface without pits.

[0022] Preferably, a 4mm×4mm central area of ​​the buccal surface of the excised tooth crown of each premolar is set as an experimental window area, and the remaining area is coated with a layer of acid-resistant nail polish and embedded with self-curing resin. After obtaining the excised tooth sample, the excised tooth sample is stored in deionized water in a constant temperature water bath at 37°C.

[0023] Preferably, the step of randomly selecting 5 of the 50 ex vivo tooth samples as normal teeth for control test, and randomly dividing the remaining 45 ex vivo tooth samples into 3 groups, with 15 ex vivo tooth samples in each group undergoing demineralization, comprises: randomly selecting 5 of the 50 ex vivo tooth samples as a blank control group according to a random number table method, and dividing the remaining 45 ex vivo tooth samples into a demineralization group, a fluoride treatment group and a remineralization group, with 15 ex vivo tooth samples in each group, and each group is further divided into 72h, 96h and 120h subgroups according to the demineralization time, with 5 ex vivo tooth samples in each subgroup;

[0024] After grouping, performance testing, biosafety testing, antibacterial performance testing, and remineralization performance testing are carried out respectively. The specific steps are as follows:

[0025] ① Detection and identification of ZIF-8@nHA: Prepare MOFs ZIF-8 and load nHA to obtain the composite remineralizer ZIF-8@nHA; use PXRD (polycrystalline powder diffraction) and SEM (scanning electron microscope) to characterize the crystal state, morphology and growth distribution of the material on the substrate; use N2 adsorption and desorption, FT-IR (Fourier transform infrared spectroscopy) and EDS (electron energy spectrometer) to analyze the pore characteristics and surface composition of the material; use ICP (inductively coupled plasma spectrometer) and UV-Vis (ultraviolet visible spectrophotometer) to analyze the release of the remineralizer nHA in the composite material, and explore the sustained release of the remineralizer nHA in ZIF-8@nHA.

[0026] ② In vitro test of biocompatibility of ZIF-8@nHA-aligner: Toxicity-sensitive L-929 cells and human gingival fibroblasts were used as research objects to detect the effect of ZIF-8@nHA on cell proliferation activity and extension adhesion.

[0027] ③ Antibacterial property test of ZIF-8@nHA-aligner: Streptococcus mutans, a recognized major cariogenic bacterium, was taken as the research object. The bacterial colony unit counting method was used to detect the antibacterial proliferation activity of ZIF-8@nHA. The live / dead bacteria fluorescence staining method was used to detect the bactericidal and anti-adhesion properties of ZIF-8@nHA. SEM was used to observe the bacterial morphology after ZIF-8@nHA coating treatment, and the antibacterial mechanism of the coating was analyzed.

[0028] ④ In vitro remineralization experiment simulating oral environment: ZIF-8 was loaded on the braces and stored with nHA remineralizer. The crystal state, morphology and growth distribution of the material on the matrix were characterized by PXRD and SEM, and the micro-Vickers surface hardness (SMH) was detected to explore the remineralization effects of the control group and the experimental groups on demineralized teeth to different degrees.

[0029] The beneficial effects of the present invention are as follows: the present invention senses and releases the mineralizer nHA through phosphate stimulation and acidic environment, and can maintain the appropriate calcium-phosphorus ion concentration (calcium-phosphorus ratio of 1.63) required for remineralization of the enamel surface for a relatively long time in the relatively low exchange and low flow saliva environment in the braces, ensuring the mineral ion deposition and crystal growth time required for remineralization, and maintaining the remineralization effect; the antibacterial properties of the MOF@nHA composite material and the PH intelligent sensing design induce the regeneration of the mineralized tooth tissue microstructure; the positioning modification of the invisible braces improves the targeted remineralization treatment The accuracy of the material was tested; by synthesizing ZIF-8@nHA remineralization materials and modifying them on the surface of invisible braces, the effectiveness of invisible braces in preventing and treating WSL was explored, and new ideas were found for reducing WSL in patients with invisible braces; key factors such as the loading concentration of mineralizers and the controlled release time for stable remineralization were explored to provide experimental basis for the early realization of clinical transformation and application; in this study, (nHA) and ZIF-8MOF were combined to prepare ZIF-8@nHAMOFs composite materials, and the release of nHA and Zn2+ was observed and recorded to explore its biosafety and antibacterial properties. At the same time, MOFs@nHA was modified on transparent braces to carry out in vitro studies on remineralization treatment, and the remineralization effect was evaluated from both quantitative and qualitative aspects through electron microscopy, hardness testing and other detection methods. It will provide preliminary experimental basis and new ideas for material modification for improving the prevention and treatment of WSL with invisible braces. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the prior art description. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.

[0031] Figure 1 It is a schematic flow chart of an in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance provided in an embodiment of the present invention;

[0032] Figure 2 This is the SEM image of the demineralized tooth sample;

[0033] Figure 3 is a scanning electron micrograph of a demineralized tooth after remineralization using ZIF-8@nHA through in vitro pH cycling provided by an embodiment of the present invention;

[0034] Figure 4 This is a before and after comparison diagram of the braces loaded with ZIF-8@nHA provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to make the technical personnel in the technical field better understand the scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in combination with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, device, product or end including a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or units inherent to these processes, methods, products or ends.

[0037] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0038] At present, there is no research report on the use of MOF-loaded remineralizers for tooth enamel remineralization. Our research group has successfully realized the use of MOFs remineralization drugs on invisible braces, and obtained a relatively reliable preliminary experimental basis. In this study, (nHA) and ZIF-8MOF were combined to prepare ZIF-8@nHA MOFs composite materials, and the nHA and Zn were observed and recorded. 2+ At the same time, MOFs@nHA was modified on transparent braces to carry out in vitro research on remineralization therapy. The remineralization effect was evaluated quantitatively and qualitatively through electron microscopy, hardness testing and other detection methods, which will provide preliminary experimental basis and new ideas for material modification to improve the prevention and treatment of WSL with invisible braces.

[0039] The present invention aims to provide an in vitro research method for preventing and treating enamel chalky plaque with ZIF-8@nHA modified invisible braces. By synthesizing ZIF-8@nHA remineralization material and modifying it on the surface of invisible braces, the effectiveness of invisible braces in preventing and treating WSL is explored, new ideas are sought to reduce WSL in invisible braces patients, and key factors such as the mineralizer loading concentration and controlled release time for stable remineralization are explored, providing an experimental basis for the early realization of clinical transformation and application.

[0040] The specific embodiment of the present invention provides an in vitro research method for preventing and treating enamel chalky plaque with a ZIF-8@nHA modified invisible brace. Figure 1 As shown, the following steps are included:

[0041] Take 2-methylimidazole and dissolve it in 50 mL of anhydrous methanol solution to obtain solution A.

[0042] In the embodiment of the present invention, 2-methylimidazole is dissolved in 50 mL of anhydrous methanol solution, and then ultrasonically homogenized to obtain solution A.

[0043] Dissolve Zn(NO3)2·6H20 in 50 mL of anhydrous methanol as solution B.

[0044] In the embodiment of the present invention, the dosage ratio of 2-methylimidazole in solution A to Zn(NO3)2·6H20 in solution B is 8:1.

[0045] Solution A was slowly added dropwise to solution B, and white ZIF-8 nanocrystals were obtained after centrifugal separation.

[0046] In an embodiment of the present invention, solution A is slowly added dropwise to solution B to obtain a mixed solution, and the mixed solution is stirred at room temperature for 1 hour, allowed to stand for 10-14 hours after stirring, and then centrifuged to obtain white ZIF-8 nanocrystals.

[0047] A one-step drug loading method was used on white ZIF-8 nanocrystals to obtain ZIF-8@nHA, such as Figure 4 shown.

[0048] In the embodiment of the present invention, a one-step drug loading method is adopted for white ZIF-8 nanocrystals to obtain ZIF-8@nHA encapsulated nHA with a particle size of 20 nm.

[0049] ZIF-8@nHA was grown and modified on the surface of the braces to obtain ZIF-8@nHA modified braces.

[0050] In an embodiment of the present invention, before ZIF-8@nHA is grown and modified on the surface of the braces, the braces need to be subjected to surface hydroxylation treatment first, and surface hydroxyl groups are increased by surface modification with dopamine for anchoring and attachment of ZIF-8@nHA; ZIF-8@nHA is grown and decorated on the braces that have been subjected to surface hydroxylation treatment to obtain ZIF-8@nHA modified braces.

[0051] The ZIF-8@nHA modified braces were demineralized using artificial demineralization fluid to obtain the enamel demineralization model.

[0052] In the embodiment of the present invention, premolars with fully developed root apex, fully developed enamel, good gloss, no caries, no fluoride and tetracycline teeth, no hidden cracks in teeth, and no pulp treatment were selected; the pigment deposits, surface soft tissues and dental calculus on the surface of the premolars were cleaned, immersed in medical saline, and stored in a refrigerator at 4°C. The immersion liquid was changed every week and the storage time was not more than one month; a 4mm×4mm central area of ​​the buccal surface of the ex vivo crown of each premolar was set as an experimental window area, and the remaining areas were coated with a layer of acid-resistant nail polish and embedded with self-curing resin to obtain an ex vivo tooth sample; 5 ex vivo tooth samples were randomly selected from 50 ex vivo tooth samples and used as normal teeth as a control test, and the remaining 45 ex vivo tooth samples were randomly divided into 3 groups, and 15 ex vivo tooth samples in each group were demineralized until chalk spots appeared on the tooth surface; before a 4mm×4mm central area of ​​the buccal surface of the ex vivo crown of each premolar was set as the experimental window area, it also included using 800 mesh and 1200 mesh. The buccal surface of the excised premolars was polished with 2400-grit carbon silicon sandpaper in sequence until it was smooth and mirror-like without pits; a 4mm×4mm central area of ​​the buccal surface of the excised crown of each premolar was set as the experimental window area, and the remaining areas were coated with a layer of acid-resistant nail polish and embedded with self-curing resin. After obtaining the excised tooth samples, the excised tooth samples were stored in deionized water in a constant temperature water bath at 37℃; 5 excised tooth samples were randomly selected from 50 excised tooth samples and used as normal teeth as controls. According to the test, the remaining 45 ex vivo tooth samples were randomly divided into 3 groups, each group with 15 ex vivo tooth samples for demineralization steps, including: 5 ex vivo tooth samples were randomly selected from 50 ex vivo tooth samples as a blank control group according to the random number table method, and the remaining 45 ex vivo tooth samples were divided into a demineralization group, a fluoride treatment group and a remineralization group, each group with 15 ex vivo tooth samples, and each group was further divided into 72h, 96h, and 120h subgroups according to the demineralization time, with 5 ex vivo tooth samples in each subgroup.

[0053] Embodiment 1

[0054] 80 mmol of 2-methylfudazole was dissolved in 50 mL of anhydrous methanol solution and then ultrasonically homogenized as solution A. 10 mmol of Zn(NO3)2·6H20 was dissolved in 50 mL of anhydrous methanol as solution B. Solution A was slowly added dropwise to solution B, stirred for 1 hour at room temperature, and then allowed to stand for 12 hours. White ZIF-8 nanocrystals were obtained by centrifugation and washed three times with anhydrous methanol. A one-step drug loading method was used to encapsulate nHA with a particle size of 20 nm to obtain ZIF-8@nHA. To grow and modify ZIF-8@nHA on the surface of braces, the orthodontic appliance needs to be surface hydroxylated first. Dopamine is used to increase the surface hydroxyl groups for the anchoring and attachment of ZIF-8@nHA to obtain ZIF-8@nHA modified braces. Artificial demineralization liquid was used for demineralization to obtain ZIF-8@nHA modified braces.

[0055] Premolars with fully developed root apex, fully developed enamel, good gloss, no caries, no fluoride, no tetracycline, no cracks, and no endodontic treatment were selected. The pigment deposits, surface soft tissues and calculus on the tooth surface were cleaned, soaked in medical saline, and stored in a refrigerator at 4°C. The soaking liquid was changed every week. The storage time should not exceed one month before the experiment began. Before the experiment, the buccal surface of the excised tooth was polished with 800 mesh, 1200 mesh, and 2400 mesh carbon silicon sandpaper in sequence until the tooth surface was smooth and mirror-like without pits. A 4mm×4mm window area was set in the central area of ​​the buccal surface of each crown as the experimental window area, and the rest of the area was coated with a layer of acid-resistant nail polish (as a comparison area). The samples were embedded with self-curing resin, and the samples were stored in deionized water and kept in a constant temperature water bath at 37°C for later use.

[0056] Five samples were randomly selected from the 50 ex vivo tooth samples as normal teeth for control testing, and the remaining 45 tooth samples were randomly divided into three groups, with 15 teeth in each group for demineralization. The model was successful when chalky spots appeared on the tooth surface.

[0057] At present, the immersion time of demineralization liquid modeling is usually 96 hours. In order to study demineralized teeth with different demineralization degrees, this experiment initially planned to select 72 hours and 120 hours for demineralization modeling at the same time around 96 hours.

[0058] According to the random number table method, 5 teeth were randomly selected from the 50 ex vivo tooth samples as the blank control group (C), and the remaining 45 teeth were divided into the demineralization group (DM), fluoride treatment group (F group), and remineralization group (RM), with 15 teeth in each group; each experimental group was further divided into 72h, 96h, and 120h subgroups according to the demineralization time, with 5 teeth in each subgroup.

[0059] (1) MOFs ZIF-8 was prepared and loaded with nHA to obtain the composite remineralizer ZIF-8@nHA. The crystal state, morphology and growth distribution of the material on the substrate were characterized by PXRD (polycrystalline powder diffraction) and SEM (scanning electron microscopy). The pore characteristics and surface composition of the material were analyzed by N2 adsorption and desorption, FT-IR (Fourier transform infrared spectroscopy) and EDS (electron spectroscopy). The release of the remineralizer nHA in the composite material was analyzed by ICP (inductively coupled plasma spectrometer) and UV-Vis (ultraviolet visible spectrophotometer), and the sustained release of the remineralizer nHA in ZIF-8@nHA was explored.

[0060] (2) In vitro biocompatibility test of ZIF-8@nHA-aligner: Toxicity-sensitive L-929 cells and human gingival fibroblasts were used as research subjects to detect the effect of ZIF-8@nHA on cell proliferation activity and stretching adhesion.

[0061] (3) Antibacterial property test of ZIF-8@nHA-aligner: Streptococcus mutans, a recognized major cariogenic bacterium, was used as the research object. The bacterial colony unit counting method was used to detect the antibacterial proliferation activity of ZIF-8@nHA. The live / dead bacteria fluorescence staining method was used to detect the bactericidal and anti-adhesion properties of ZIF-8@nHA. The bacterial morphology after ZIF-8@nHA coating treatment was observed using SEM, and the antibacterial mechanism of the coating was analyzed.

[0062] (4) In vitro remineralization experiment simulating oral environment: ZIF-8 was loaded on the braces and loaded with nHA remineralizer. The crystal state, morphology and growth distribution of the material on the matrix were characterized by PXRD and SEM. The micro-Vickers surface hardness (SMH) was also tested to explore the remineralization effects of the control group and the experimental groups on demineralized teeth to different degrees.

[0063] From a low-power microscope Figure 3 A in the figure shows that the enamel surface has a porous fish-scale appearance after demineralization, which is a typical appearance after acid etching. The enamel surface is porous and concave, and each concave represents the destruction of the end of an enamel column. Under a high-power microscope, the crystal particles formed by the dissolution and destruction of the center of the enamel column can be clearly seen, and these particles have a clearer appearance. Due to the dissolution of the enamel column interstitium, the enamel column head appears more prominent.

[0064] pass Figure 2 and Figure 3 By comparison, it can be clearly seen that after the remineralization experiment, the enamel of the demineralized tooth has been significantly repaired. The surface of the enamel of the demineralized tooth was originally very rough, showing a concave porous shape, the enamel column interstitium dissolved, and the enamel column head protruding; while the surface of the remineralized enamel is relatively smooth, the original pits have been filled with newly attached and grown nanohydroxyapatite, and the enamel column head is almost invisible, proving that drugs can be released to promote remineralization; the scanning electron microscope image of the demineralized tooth after 20 days of in vitro pH cycle remineralization using ZIF-8@nHA@TPU is compared with the SEM image of the demineralized tooth, which clearly shows that after the remineralization experiment, the enamel of the demineralized tooth has been significantly repaired.

[0065] The beneficial effects of the present invention are as follows: the present invention senses and releases the mineralizer nHA through phosphate stimulation and acidic environment, and can maintain the appropriate calcium-phosphorus ion concentration (calcium-phosphorus ratio of 1.63) required for remineralization of the enamel surface for a relatively long time in the relatively low exchange and low flow saliva environment in the braces, ensuring the mineral ion deposition and crystal growth time required for remineralization, and maintaining the remineralization effect; the antibacterial properties of the MOF@nHA composite material and the PH intelligent sensing design induce the regeneration of the mineralized tooth tissue microstructure; the positioning modification of the invisible braces improves the targeted remineralization treatment The accuracy of the material was tested; by synthesizing ZIF-8@nHA remineralization materials and modifying them on the surface of invisible braces, the effectiveness of invisible braces in preventing and treating WSL was explored, and new ideas were found for reducing WSL in patients with invisible braces; key factors such as the loading concentration of mineralizers and the controlled release time for stable remineralization were explored to provide experimental basis for the early realization of clinical transformation and application; in this study, (nHA) and ZIF-8MOF were combined to prepare ZIF-8@nHAMOFs composite materials, and the release of nHA and Zn2+ was observed and recorded to explore its biosafety and antibacterial properties. At the same time, MOFs@nHA was modified on transparent braces to carry out in vitro studies on remineralization treatment, and the remineralization effect was evaluated from both quantitative and qualitative aspects through electron microscopy, hardness testing and other detection methods. It will provide preliminary experimental basis and new ideas for material modification for improving the prevention and treatment of WSL with invisible braces.

[0066] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical schemes or characteristics in the scheme is not described in detail here; it should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the scheme of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the present invention and the practicality of the patent. The protection scope required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. An in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace appliance, characterized in that: The method comprises: Take 2-methylimidazole and dissolve it in 50 mL of anhydrous methanol solution to obtain solution A; Dissolve Zn(NO3)2·6H20 in 50 mL of anhydrous methanol as solution B; The A solution is slowly added dropwise to the B solution, and white ZIF-8 nanocrystals are obtained by centrifugation; A one-step drug loading method is used on the white ZIF-8 nanocrystals to obtain ZIF-8@nHA; Growing and modifying the ZIF-8@nHA on the surface of the brace to obtain a ZIF-8@nHA modified brace; The ZIF-8@nHA modified dental cap was demineralized using an artificial demineralizing solution to obtain a demineralized enamel model.

2. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance according to claim 1, characterized in that: After dissolving 2-methylimidazole in 50 mL of anhydrous methanol solution, ultrasonic homogenization is required to obtain solution A.

3. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace appliance according to claim 1, characterized in that: The dosage ratio of the 2-methylpyrazole in the A solution and the Zn(NO3)2·6H20 in the B solution is 8:

1.

4. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance according to claim 1, characterized in that: The A solution is slowly added dropwise to the B solution to obtain a mixed solution, and the mixed solution is stirred at room temperature for 1 hour, allowed to stand for 10-14 hours after stirring, and then centrifuged to obtain white ZIF-8 nanocrystals.

5. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace appliance according to claim 1, characterized in that: The white ZIF-8 nanocrystals were subjected to a one-step drug loading method to obtain ZIF-8@nHA encapsulated nHA with a particle size of 20 nm.

6. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance according to claim 1, characterized in that: Before the ZIF-8@nHA is grown and modified on the surface of the braces, the braces need to be subjected to surface hydroxylation treatment, and the surface hydroxyl groups are increased by surface modification with dopamine for the anchoring and attachment of the ZIF-8@nHA. The ZIF-8@nHA is grown and decorated onto the braces that have been subjected to surface hydroxylation treatment to obtain ZIF-8@nHA modified braces.

7. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace appliance according to claim 1, characterized in that: The step of demineralizing the ZIF-8@nHA modified dental cap by using an artificial demineralizing solution to obtain a tooth enamel demineralization model comprises: Premolars with fully developed root apex, fully developed enamel, good gloss, no caries, no fluoride, no tetracycline, no cracks, and no endodontic treatment were selected; Clean the pigment deposits, surface soft tissues and dental calculus on the surface of the premolars, immerse them in medical saline, store them in a refrigerator at 4°C, change the immersion liquid every week, and store them for no more than one month; A 4 mm × 4 mm window area was set in the central area of ​​the buccal surface of each premolar as an experimental window area, and the remaining area was coated with a layer of acid-resistant nail polish and embedded with self-curing resin to obtain an isolated tooth sample; Five of the 50 ex vivo tooth samples were randomly selected to serve as normal teeth for control testing, and the remaining 45 ex vivo tooth samples were randomly divided into three groups, with 15 ex vivo tooth samples in each group undergoing demineralization until chalky spots appeared on the tooth surface.

8. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible brace appliance according to claim 7, characterized in that: Before setting a 4mm×4mm central area of ​​the buccal surface of the ex vivo crown of each premolar as the experimental window area, the method also includes polishing the ex vivo buccal surface of the premolar with 800-mesh, 1200-mesh, and 2400-mesh carbon silicon sandpaper in sequence until the ex vivo buccal surface is smooth and mirror-like without pits.

9. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance according to claim 7, characterized in that: A 4mm×4mm experimental window area was set in the central area of ​​the buccal surface of each premolar, and the remaining area was coated with a layer of acid-resistant nail polish and embedded with self-curing resin. After obtaining the tooth sample, the tooth sample was stored in deionized water in a constant temperature water bath at 37°C.

10. The in vitro research method for preventing and treating enamel chalky plaques using a ZIF-8@nHA modified invisible appliance according to claim 7, characterized in that: The step of randomly selecting 5 of the 50 ex vivo tooth samples as normal teeth for control testing, and randomly dividing the remaining 45 ex vivo tooth samples into 3 groups, with 15 ex vivo tooth samples in each group undergoing demineralization, comprises: According to the random number table method, 5 of the 50 ex vivo tooth samples were randomly selected as a blank control group, and the remaining 45 ex vivo tooth samples were divided into a demineralization group, a fluoride treatment group and a remineralization group, with 15 ex vivo tooth samples in each group. Each group was further divided into 72h, 96h, and 120h subgroups according to the demineralization time, with 5 ex vivo tooth samples in each subgroup.